Repeated observations of a Cape Gannet Morus capensis on the coast of Patagonia, Argentina - Rebstock, Ginger A. (2010)
The Cape Gannet Morus capensis (Lichtenstein, 1823) is a seabird endemic to southern Africa, breeding at only six localities, three in Namibia and three in South Africa. The population is currently estimated to be 151 000 pairs (Crawford et al. 2007). After the breeding season, some Cape Gannets disperse north, along the west coast of Africa, while many follow sardine Sardinops sagax schools eastward. The species is usually restricted to the continental shelf of Africa and rarely seen more than a few hundred kilometres offshore (Crawford 2005). In spite of this relatively restricted distribution, vagrants of this species have been reported in Australia, New Zealand, Amsterdam Island (Indian Ocean), Spain, Argentina, Brazil and Perú (Berteaux 1991, Ramírez Llorens 1996, García-Godos 2002, Vooren 2004, Crawford 2005).